MONITORING PLTS BATTERY ENERGY STORAGE ON SALT PRODUCTION TOOLS - Rayhan, Akbar; Jamaaluddin, Jamaaluddin; Ayuni, Shazana Dhiya; Syahrorini, Syamsudduha (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2025)
Indonesia, being on the equator, possesses significant solar energy potential with an average radiation intensity of 4.8 kWh/m² per day. This potential can be utilised for various sectors, including the salt production industry which requires a stable electricity supply. Solar Power Plant (PLTS) is a strategic alternative in increasing the efficiency of salt production, especially in the drying stage. This study aims to analyse the performance of the energy storage system in the solar power plant battery used in the salt production process. The research method involved measuring the voltage from the solar panel stored in the battery through three daily testing sessions. The test results showed that the highest voltage, 12.59 Volts, was reached in the morning and afternoon, while in the afternoon it decreased as the intensity of sunlight decreased. The results of this study show that solar power plants play an important role in maintaining a stable supply of electrical energy to support salt production. However, voltage fluctuations due to changes in sunlight intensity emphasise the importance of optimising the energy storage system. Therefore, the development of more efficient storage technologies is needed to increase the effectiveness of renewable energy-based salt production.